Perinatal Hypoxia and Ischemia in Animal Models of Schizophrenia - Hefter, Dimitri; Marti, Hugo H.; Gass, Peter; Inta, Dragos (Frontiers in Psychiatry, 2018)
Intrauterine or perinatal complications constitute a major risk for psychiatric diseases. Infants who suffered from hypoxia-ischemia are at twofold risk to develop schizophrenia in later life. Several animal models attempt to reproduce these complications in order to study the yet unknown steps between an insult in early life and outbreak of the disease decades later. However, it is very challenging to find the right type and severity of insult leading to a disease-like phenotype in the animal, but not causing necrosis and focal neurological deficits. In contrast, too mild, repetitive insults may even be protective via conditioning effects. Thus it is not surprising that animal models of hypoxia lead to mixed results. To achieve clinically translatable findings, better protocols are urgently needed. Therefore we compare widely used models of hypoxia and hypoxia-ischemia and propose future directions for the field.